Gender and International Revenue - Septiyanti, Ratna (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study's primary objective is to empirically examine the impact of gender composition in the workforce on government revenue at the international level. The labor market is essential in accounting and economics due to its significant role in shaping an economy. This study utilizes a comprehensive dataset of observations from 202 nations globally over ten years. The study's empirical findings highlight the crucial significance of efficient governance in labor markets. The correlation between male labor force participation and government revenue highlights the importance of gender dynamics in the workforce as a potentially critical factor in economic outcomes. This observation stimulates additional investigation into the methods and policies promoting fairer and more efficient labor markets, leading to increased government income and excellent overall financial stability.